Single-layer silica gel spiral heating wire and preparation method thereof
Patent Information
- Application Number
- CN202611048607.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-15
- Publication Date
- 2026-10-20
AI Technical Summary
[0007]本发明的目的是提供一种单层硅胶螺旋发热线及其制备方法,以解决现有硅胶发热线在导热性能、阻燃安全性和耐高温老化能力方面难以协同提升,以及芯线与硅胶护套之间因界面结合力弱导致长期运行可靠性不足的问题,实现发热线在综合性能上的平衡与优化
[0041]本发明通过配方体系与芯线结构两方面的协同改进,在多项性能上实现了综合优化。在导热方面,采用聚多巴胺与单宁酸共沉积改性的碳纳米管/六方氮化硼混杂填料,填料表面包覆的有机层与硅橡胶基体浸润性良好,一维管状与二维片状填料的复配在较低填充量下构建了高效导热网络,导热系数可达1.35W/(m·K)以上,同时避免了高填充量对硅橡胶柔韧性的损害,断裂伸长率保持在310%以上。在阻燃方面,聚磷酸铵与三聚氰胺氰尿酸盐复配形成氮-磷协效膨胀阻燃体系,辅以硼酸锌在高温下形成玻璃态包覆膜增强炭层并抑烟,产品极限氧指数达到33.8%以上,垂直燃烧等级V-0级,且燃烧不释放卤化氢等腐蚀性气体。在耐热老化方面,纳米氧化铈通过变价捕捉自由基、八乙烯基POSS作为多官能度交联点锚定网络、碳化硼提供物理骨架支撑,三者协同作用使125℃×168h热空气老化后拉伸强度保留率保持在89%以上。在结构可靠性方面,芯线表面预浸的导电高分子界面层通过KH550的硅烷端与玻璃纤维形成共价键,聚氨酯层与硅橡胶模量匹配消除了界面突变,导电炭黑在发热丝意外断裂时提供微弱导电旁路,该界面层使成品发热线在热老化后仍能承受25000次以上弯曲循环,500次通电循环电阻变化率低于1%,显著延长了发热线的使用寿命。
Smart Images

Figure FT_1 
Figure FT_2 
Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrothermal materials technology, specifically relating to a single-layer silicone spiral heating wire and its preparation method. Background Technology
[0002] Silicone heating wire is a flexible electric heating product that uses an alloy heating wire as the heating element and silicone rubber as the insulating protective layer. Due to its excellent temperature resistance, electrical insulation, and flexibility, it has been widely used in household appliances, medical therapy, wearable heating, and pipeline heat tracing. A typical silicone heating wire adopts a composite structure of "glass fiber core wire—spiral wound heating wire—silicone rubber sheath," with glass fiber serving as the mechanical support skeleton. The heating alloy wire is spirally wound on its surface to form the heating element, and the outermost layer is extruded and coated with a silicone rubber insulating sheath. However, as application scenarios increasingly demand higher heating power density, long-term operational reliability, and safety levels, the shortcomings of this traditional structure in terms of thermal management, flame retardant safety, and durability are becoming increasingly apparent.
[0003] In terms of thermal conductivity, ordinary silicone rubber has a thermal conductivity of only about 0.2 W / (m·K). The heat generated by the heating wire is difficult to conduct efficiently to the surface of the wire, easily leading to heat accumulation inside, causing localized overheating and even accelerating material aging. To improve the thermal conductivity of silicone rubber, CN117210015A discloses a silicone rubber composite material that, by adding modified thermally conductive fillers containing amino, epoxy, or carboxyl groups (such as boron nitride, graphene, and carbon nanotubes), achieves high thermal conductivity while maintaining certain mechanical properties. CN114213850B uses a compound of boron nitride and polydopamine-modified graphene as a thermally conductive filler to construct a thermally conductive network within the silicone rubber matrix, and adds flame retardants and silane coupling agents to also consider flame retardant properties. However, while the above solutions each have their own focus on thermal conductivity and flame retardancy, the large addition of thermally conductive fillers often comes at the cost of sacrificing the flexibility and tear strength of silicone rubber. In particular, when the filler content exceeds a certain threshold, the hardness of the silicone layer increases sharply and the elongation at break decreases significantly, which makes the heating wire prone to sheath cracking during repeated bending or winding.
[0004] In terms of flame retardancy and safety, heating wires must possess sufficient flame retardancy to prevent fires under fault conditions (such as partial short circuits or overheating). Metal hydroxides are commonly used halogen-free flame retardants, but their flame retardancy efficiency is relatively low, typically requiring a high filler content of over 50 parts to achieve a V-0 flame retardancy rating, severely degrading the mechanical flexibility of silicone rubber. Intumescent flame retardants (IFRs), through the synergistic effect of acid, carbon, and gas sources, can achieve highly efficient flame retardancy at lower addition levels, and phosphorus-nitrogen compound systems can also exert a synergistic flame retardant effect. However, existing silicone heating wire formulations generally suffer from the problem of balancing flame retardancy and flexibility—if flame retardancy is sacrificed for flexibility, the product's safety level is insufficient; if a large amount of inorganic flame retardant is added for flame retardancy, the silicone layer becomes brittle and prone to cracking.
[0005] Regarding durability and interface reliability, silicone rubber is continuously subjected to heat and oxygen during long-term operation of the heating wire. The side methyl groups of the siloxane main chain undergo oxidative breakage under the combined action of high temperature and oxygen, causing the silicone layer to gradually harden and crack, losing its insulating protective function. CN118562298A improves the flame retardancy and high-temperature aging resistance of silicone rubber by compounding modified aluminum hydroxide and graphene-TiO2-Fe2O3 composite materials, but its thermal conductivity has not been systematically optimized. In addition, the interfacial bonding between the glass fiber core wire, the heating alloy wire, and the silicone sheath is weak, and the thermal expansion coefficients of the two materials differ greatly. After long-term use in hot and cold cycles, micro-voids are easily generated at the interface, which not only increases the interlayer thermal resistance and reduces the heat conduction efficiency, but may also cause fretting wear or even breakage of the heating wire.
[0006] In summary, existing silicone heating wires suffer from multiple challenges in achieving synergistic improvements in thermal conductivity, flame retardancy, aging resistance, and interface reliability. There is an urgent need for a silicone heating wire that achieves a comprehensive balance in terms of thermal conductivity, flame retardancy, high-temperature aging resistance, and interface bonding reliability. Summary of the Invention
[0007] The purpose of this invention is to provide a single-layer silicone spiral heating wire and its preparation method, so as to solve the problems that existing silicone heating wires are difficult to improve in terms of thermal conductivity, flame retardancy and high temperature aging resistance, as well as the problem that the weak interfacial bonding between the core wire and the silicone sheath leads to insufficient long-term operational reliability, thereby achieving a balance and optimization of the heating wire's overall performance.
[0008] To achieve the above objectives, the present invention provides the following technical solution:
[0009] The first aspect of this invention provides a single-layer silicone spiral heating wire, comprising a core wire and a silicone rubber sheath covering the outer surface of the core wire. The core wire comprises a glass fiber skeleton and a heating alloy wire spirally wound around the surface of the glass fiber skeleton. The silicone rubber sheath is prepared from the following raw materials in parts by weight:
[0010] 100 parts of raw methyl vinyl silicone rubber;
[0011] 30-50 parts of surface-functionalized modified composite thermally conductive filler;
[0012] 20-30 parts of nitrogen-phosphorus synergistic halogen-free flame retardant;
[0013] 5-10 parts of composite heat resistant agent;
[0014] 1.5 to 2.5 parts of vulcanizing agent;
[0015] 3-5 parts zinc borate;
[0016] The surface-functionalized composite thermally conductive filler is obtained by surface modification of a compound of carbon nanotubes and hexagonal boron nitride nanosheets with polydopamine and tannic acid.
[0017] The composite heat-resistant agent is composed of nano-cerium oxide, octavinylPOSS (octavinyloctasilylsesquioxane), and nano-boron carbide.
[0018] Furthermore, the preparation method of the surface-functionalized modified composite thermally conductive filler includes the following steps:
[0019] (1) Carbon nanotubes and hexagonal boron nitride nanosheets were mixed and added to an aqueous solution of sodium hydroxide. After ultrasonic stirring, centrifugation, washing with deionized water, and drying, hydroxylated composite thermally conductive filler was obtained.
[0020] (2) Prepare a Tris (tris(hydroxymethyl)aminomethane) buffer solution with a concentration of 1.0-1.5 g / L, and adjust the pH value to 8.0-8.5 with dilute hydrochloric acid; disperse the hydroxylated composite thermally conductive filler obtained in step (1) in the Tris buffer solution, add dopamine hydrochloride and tannic acid, stir and react for 6-12 hours, and after the reaction is completed, centrifuge, wash with deionized water and dry to obtain the surface functionalized modified composite thermally conductive filler.
[0021] Furthermore, in step (1), the weight ratio of carbon nanotubes to hexagonal boron nitride nanosheets is 1:2 to 1:5; and the concentration of sodium hydroxide aqueous solution is 8 to 12 g / L.
[0022] Furthermore, in step (2), the mass ratio of the hydroxylated composite thermally conductive filler, dopamine hydrochloride, and tannic acid is (6-10):(2-4):1.
[0023] Carbon nanotubes possess extremely high thermal conductivity along their axial direction. However, when used alone, their large aspect ratio and high specific surface area make them prone to entanglement and aggregation in silicone rubber, hindering the formation of uniform thermal conductive pathways. Hexagonal boron nitride nanosheets, with their two-dimensional layered structure and high in-plane thermal conductivity, act as bridges between the layers when combined with carbon nanotubes, connecting the boron nitride sheets that were originally separated by the matrix and forming a continuous thermal conductive network. However, both fillers have high surface energy and poor compatibility with silicone rubber, resulting in high interfacial thermal resistance and limited improvement in thermal conductivity when directly blended. After co-deposition modification with polydopamine and tannic acid, the filler surface is coated with an organic layer rich in catechol groups, significantly improving its wettability with the silicone rubber matrix. This enhances the uniformity of filler dispersion and interfacial bonding in the matrix, reducing the interfacial thermal resistance at the filler-matrix interface. This allows heat to be efficiently transferred along the thermal conductive network with a lower filler content, while avoiding the deterioration of silicone flexibility caused by high filler content.
[0024] Furthermore, the nitrogen-phosphorus synergistic halogen-free flame retardant is compounded from ammonium polyphosphate and melamine cyanurate in a weight ratio of (2-4):1.
[0025] Ammonium polyphosphate decomposes upon heating to release phosphoric acid and polyphosphoric acid, promoting the dehydration and charring of silicone rubber to form a carbon-rich layer. Simultaneously, ammonia gas is released to dilute gaseous combustibles. Melamine cyanurate decomposes at even higher temperatures, releasing inert gases that cause the char layer to foam and expand, forming a porous expanded layer, further enhancing its heat and oxygen insulation effects. When combined, ammonium polyphosphate first decomposes and catalyzes charring, followed by melamine cyanurate foaming and expanding. The charring and foaming processes work in succession at different temperatures, resulting in a dense and thick expanded char layer with higher flame retardant efficiency than when using a single component. Furthermore, zinc borate added to the formulation melts at high temperatures to form a glassy film covering the char layer surface, enhancing its strength and suppressing smoke. This system is halogen-free and does not release corrosive gases during combustion.
[0026] Furthermore, the mass ratio of the nano-cerium oxide, octavinyl POSS, and nano-boron carbide is (0.3-0.6):(0.4-0.8):1.
[0027] The performance degradation of silicone rubber during high-temperature use mainly stems from two factors: firstly, the oxidative breakage of side methyl groups under thermo-oxidative conditions; and secondly, the rearrangement and degradation of the main chain siloxane bonds at high temperatures. In the composite heat-resistant agent of this invention, nano-cerium oxide possesses Ce... 3+ / Ce 4+The variable valence capability allows it to capture peroxide free radicals generated during the thermo-oxidative aging of silicone rubber, interrupting the oxidation chain reaction, which is a chemical antioxidant mechanism. Octadecylvinyl POSS contains a rigid inorganic silica cage core and eight vinyl groups that can participate in crosslinking. During vulcanization, it acts as a multifunctional crosslinking point, bonding into the silicone rubber network and uniformly anchoring the nanoscale rigid cage structure at the crosslinking points, restricting the thermal movement of siloxane segments and improving the thermal and dimensional stability of the network. Nano-boron carbide has extremely high thermal stability and thermal conductivity, acting as a physical heat-resistant skeleton in the system. It does not undergo phase change at high temperatures and can rapidly conduct and disperse locally accumulated heat, reducing the heat load at hot spots. When these three are combined, cerium oxide captures free radicals at the chemical level, POSS locks the network structure at the molecular level, and boron carbide provides rigid support and heat conduction at the physical level, forming a multi-level synergistic heat-resistant mechanism.
[0028] Furthermore, the surface of the glass fiber skeleton is pre-impregnated with a conductive polymer interface layer. The conductive polymer interface layer is prepared by mixing waterborne polyurethane emulsion, silane coupling agent KH550 and conductive carbon black, followed by dip coating and drying to form a film. The silane coupling agent KH550 accounts for 1.5% to 2.5% of the total solid mass of the waterborne polyurethane emulsion, and the conductive carbon black accounts for 5 to 10 wt% of the total solid mass of the waterborne polyurethane emulsion.
[0029] Furthermore, the method for preparing the conductive polymer interface layer is as follows:
[0030] (1) Add waterborne polyurethane emulsion with a solid content of 30-40 wt% to deionized water to dilute to a working solution with a solid content of 10-15 wt%. Add silane coupling agent KH550 and conductive carbon black under stirring to obtain impregnation solution.
[0031] (2) The glass fiber skeleton is immersed in the impregnation solution, and after being dipped and removed, it is dried at 80-100°C to form a film, that is, the conductive polymer interface layer is formed on the surface of the glass fiber skeleton.
[0032] The glass fiber skeleton has a smooth surface and strong chemical inertness. Its interfacial bonding with the heating alloy wire and silicone rubber sheath mainly relies on weak interactions such as mechanical friction and hydrogen bonding. During long-term use, differences in thermal expansion and contraction can easily lead to interlayer micro-slippage and delamination. After pre-impregnating the glass fiber surface with a water-based polyurethane-KH550-conductive carbon black composite emulsion, the silane end of KH550 condenses with the silanol groups on the glass fiber surface to form Si-O-Si covalent bonds, while the amino group at the other end is compatible with the polyurethane segments, ensuring a firm adhesion of the interfacial layer to the fiber surface. The flexibility of the polyurethane layer is close to that of the silicone rubber matrix, allowing for physical entanglement and partial chemical bonding with the silicone rubber during vulcanization, eliminating the abrupt change in modulus between the glass fiber and silicone rubber. The conductive carbon black imparts a certain degree of conductivity to the interfacial layer. When the heating alloy wire experiences localized breakage due to repeated bending, the interfacial layer can act as a weak conductive bypass to maintain the current path, preventing overall failure due to a single-point breakage. Simultaneously, the interfacial layer fills the microscopic gaps between the fiber and the heating wire, eliminating air gaps and reducing interlayer contact thermal resistance.
[0033] Furthermore, the heating alloy wire is a nickel-chromium alloy wire or a constantan wire.
[0034] The second aspect of this invention provides a method for preparing the above-mentioned single-layer silicone spiral heating wire, comprising the following steps:
[0035] (1) The heating alloy wire is wound in a spiral manner on the surface of a glass fiber skeleton pre-impregnated with a conductive polymer interface layer to obtain the core wire;
[0036] (2) Methyl vinyl silicone rubber raw rubber, surface functionalized modified composite thermally conductive filler, nitrogen-phosphorus synergistic halogen-free flame retardant, composite heat resistant agent, zinc borate and vulcanizing agent are added into a mixing mill according to the weight ratio described above and mixed to obtain silicone rubber compound.
[0037] (3) Pass the core wire obtained in step (1) through the center of the extruder head, feed the silicone rubber compound obtained in step (2) into the extruder, extrude and coat the core wire surface, and obtain the single-layer silicone spiral heating wire after vulcanization.
[0038] Furthermore, in step (2), the mixing temperature is 110-130°C and the mixing time is 15-30 minutes.
[0039] Further, in step (3), the extruder head temperature is 50-85℃, and the first temperature zone is set to 50-60℃, the second temperature zone to 60-75℃, and the third temperature zone to 75-85℃ along the extrusion direction; the vulcanization is carried out by hot air vulcanization, the vulcanization temperature is 180-250℃, and the vulcanization time is 3-8 minutes.
[0040] Compared with the prior art, the advantages and beneficial effects of the present invention are as follows:
[0041] This invention achieves comprehensive optimization in multiple performance aspects through synergistic improvements in both the formulation system and the core wire structure. Regarding thermal conductivity, a hybrid filler of carbon nanotubes / hexagonal boron nitride, co-deposited with polydopamine and tannic acid, is used. The organic layer coating the filler surface exhibits good wettability with the silicone rubber matrix. The combination of one-dimensional tubular and two-dimensional sheet-like fillers constructs a highly efficient thermally conductive network at a relatively low filler content, achieving a thermal conductivity of over 1.35 W / (m·K), while avoiding the damage to the flexibility of silicone rubber caused by high filler content, maintaining an elongation at break above 310%. In terms of flame retardancy, ammonium polyphosphate and melamine cyanurate are combined to form a nitrogen-phosphorus synergistic intumescent flame-retardant system. Zinc borate is then used to form a glassy coating at high temperatures to enhance the char layer and suppress smoke. The product achieves a limiting oxygen index of over 33.8%, a vertical burning rating of V-0, and does not release corrosive gases such as hydrogen halides during combustion. In terms of heat aging resistance, nano-cerium oxide captures free radicals through variable valence, octavinyl POSS acts as a multifunctional cross-linking point anchoring network, and boron carbide provides physical framework support. The synergistic effect of these three elements ensures that the tensile strength retention rate remains above 89% after 125℃×168h hot air aging. In terms of structural reliability, the conductive polymer interface layer pre-impregnated on the core wire surface forms covalent bonds with the glass fiber through the silane end of KH550. The polyurethane layer and silicone rubber modulus match to eliminate interface abrupt changes, and the conductive carbon black provides a weak conductive bypass in the event of accidental breakage of the heating wire. This interface layer enables the finished heating wire to withstand more than 25,000 bending cycles after heat aging, and the resistance change rate after 500 energized cycles is less than 1%, significantly extending the service life of the heating wire. Attached Figure Description
[0042] Figure 1 The image shows the actual cross-sectional structure of the end of the single-layer silicone spiral heating wire prepared in Example 1.
[0043] Figure 2 The image shows the finished product appearance of the single-layer silicone spiral heating wire prepared in Example 1. Detailed Implementation
[0044] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0045] Unless otherwise specified, all raw materials used in the embodiments are commercially available products. The following sources are illustrative examples.
[0046] The aqueous polyurethane emulsion was purchased from Beijing Kemete Technology Development Co., Ltd., and the Covestro Impranil® DAA was purchased from Beijing Deco Island Gold Technology Co., Ltd., and the CNT105 was purchased from Beijing Deco Island Gold Technology Co., Ltd.; the hexagonal boron nitride nanosheets were purchased from Zhejiang Yamei Nanotechnology Co., Ltd., and the YN-HBN-S was purchased from Zhejiang Yamei Nanotechnology Co., Ltd.; the nano-cerium oxide was purchased from Shanghai Maclean Biochemical Technology Co., Ltd., and the C804512 was purchased from Shanghai Maclean Biochemical Technology Co., Ltd.; the octavinyl POSS was purchased from Beyotime Biotechnology Co., Ltd.; and the nano-boron carbide was purchased from Shanghai Xiaohuang Nanotechnology Co., Ltd., and the XH-B4C-50 was purchased from Shanghai Xiaohuang Nanotechnology Co., Ltd.
[0047] Example 1
[0048] This embodiment provides a single-layer silicone spiral heating wire, including a core wire and a silicone rubber sheath covering the outer surface of the core wire.
[0049] The core wire comprises a glass fiber skeleton and a heating alloy wire spirally wound around the surface of the glass fiber skeleton. The glass fiber skeleton is E-glass fiber yarn with a diameter of 0.8 mm; the heating alloy wire is a nickel-chromium alloy wire with a diameter of 0.12 mm and a spiral winding pitch of 1.5 mm.
[0050] The surface of the glass fiber skeleton is pre-impregnated with a conductive polymer interface layer, and the method for preparing the conductive polymer interface layer is as follows:
[0051] (1) Add waterborne polyurethane emulsion with a solid content of 35wt% to deionized water to dilute to a working solution with a solid content of 12wt%. Add silane coupling agent KH550 and conductive carbon black under stirring, wherein silane coupling agent KH550 accounts for 2% of the total solid mass of the waterborne polyurethane emulsion and conductive carbon black accounts for 8wt% of the total solid mass of the waterborne polyurethane emulsion. Stir evenly to obtain impregnation solution.
[0052] (2) Immerse the glass fiber skeleton in the impregnation solution for 4 minutes, then remove it and dry it at 90°C for 45 minutes to form a film, that is, form the conductive polymer interface layer on the surface of the glass fiber skeleton.
[0053] The silicone rubber sheath is prepared from the following raw materials in parts by weight: 100 parts of methyl vinyl silicone rubber raw rubber; 40 parts of surface functionalized modified composite thermally conductive filler; 25 parts of nitrogen-phosphorus synergistic halogen-free flame retardant; 8 parts of composite heat resistant agent; 2 parts of vulcanizing agent 2,4-dichlorobenzoyl peroxide (DCBP); and 4 parts of zinc borate.
[0054] The preparation method of the surface-functionalized modified composite thermally conductive filler is as follows:
[0055] (1) Carbon nanotubes and hexagonal boron nitride nanosheets were mixed at a weight ratio of 1:3 and added to a sodium hydroxide aqueous solution with a concentration of 10 g / L. The mixture was ultrasonically stirred at 60 °C for 2 hours, centrifuged, washed with deionized water until neutral, and vacuum dried to obtain hydroxylated composite thermal conductive filler.
[0056] (2) Prepare a Tris buffer solution with a concentration of 1.2 g / L and adjust the pH value to 8.2 with dilute hydrochloric acid; disperse the hydroxylated composite thermal conductive filler obtained in step (1) in the Tris buffer solution, add dopamine hydrochloride and tannic acid, wherein the mass ratio of hydroxylated composite thermal conductive filler, dopamine hydrochloride and tannic acid is 8:3:1, stir the reaction at room temperature for 8 hours, after the reaction is completed, centrifuge, wash with deionized water and vacuum dry to obtain the surface functionalized modified composite thermal conductive filler.
[0057] The nitrogen-phosphorus synergistic halogen-free flame retardant is composed of ammonium polyphosphate and melamine cyanurate in a weight ratio of 3:1.
[0058] The composite heat-resistant agent is composed of nano-cerium oxide, octavinyl POSS, and nano-boron carbide in a weight ratio of 0.4:0.6:1.
[0059] The preparation method of the above-mentioned single-layer silicone spiral heating wire includes the following steps:
[0060] (1) The heating alloy wire is wound in a spiral manner around the surface of the glass fiber skeleton pre-impregnated with a conductive polymer interface layer to obtain a core wire;
[0061] (2) The methyl vinyl silicone rubber raw rubber, the surface functionalized modified composite thermally conductive filler, the nitrogen-phosphorus synergistic halogen-free flame retardant, the composite heat resistant agent, zinc borate and vulcanizing agent are added into a kneader and mixed in the weight ratio described above. The mixing temperature is 120°C and the mixing time is 20 minutes to obtain silicone rubber compound.
[0062] (3) Pass the core wire obtained in step (1) through the center of the extruder head, and feed the silicone rubber compound obtained in step (2) into the extruder. The extruder head is set to the first temperature zone 55°C, the second temperature zone 65°C and the third temperature zone 80°C in sequence along the extrusion direction. The extruded core wire is coated on the surface and vulcanized with hot air at a temperature of 220°C for 5 minutes to obtain the single-layer silicone spiral heating wire.
[0063] Figure 1 The image shows the actual cross-sectional structure of the end of the single-layer silicone spiral heating wire prepared in Example 1.
[0064] Figure 2 The image shows the finished product appearance of the single-layer silicone spiral heating wire prepared in Example 1.
[0065] Example 2
[0066] This embodiment provides a single-layer silicone spiral heating wire, including a core wire and a silicone rubber sheath covering the outer surface of the core wire.
[0067] The core wire comprises a glass fiber skeleton and a heating alloy wire spirally wound around the surface of the glass fiber skeleton. The glass fiber skeleton is E-glass fiber yarn with a diameter of 0.6 mm; the heating alloy wire is constantan wire with a diameter of 0.10 mm and a spiral winding pitch of 1.2 mm.
[0068] The surface of the glass fiber skeleton is pre-impregnated with a conductive polymer interface layer, and the method for preparing the conductive polymer interface layer is as follows:
[0069] (1) Add waterborne polyurethane emulsion with a solid content of 38 wt% to deionized water to dilute to a working solution with a solid content of 14 wt%. Add silane coupling agent KH550 and conductive carbon black under stirring, wherein silane coupling agent KH550 accounts for 2.2% of the total solid mass of the waterborne polyurethane emulsion and conductive carbon black accounts for 6 wt% of the total solid mass of the waterborne polyurethane emulsion. Stir evenly to obtain impregnation solution.
[0070] (2) Immerse the glass fiber skeleton in the impregnation solution for 3 minutes, then remove it and dry it at 85°C for 50 minutes to form a film, that is, form the conductive polymer interface layer on the surface of the glass fiber skeleton.
[0071] The silicone rubber sheath is prepared from the following raw materials in parts by weight: 100 parts of methyl vinyl silicone rubber raw rubber; 45 parts of surface functionalized modified composite thermally conductive filler; 22 parts of nitrogen-phosphorus synergistic halogen-free flame retardant; 6 parts of composite heat resistant agent; 2 parts of vulcanizing agent 2,4-dichlorobenzoyl peroxide; and 4 parts of zinc borate.
[0072] The preparation method of the surface-functionalized modified composite thermally conductive filler is as follows:
[0073] (1) Carbon nanotubes and hexagonal boron nitride nanosheets were mixed at a weight ratio of 1:4 and added to a sodium hydroxide aqueous solution with a concentration of 9 g / L. The mixture was ultrasonically stirred at 58 °C for 2.5 hours, centrifuged, washed with deionized water until neutral, and vacuum dried to obtain hydroxylated composite thermal conductive filler.
[0074] (2) Prepare a Tris buffer solution with a concentration of 1.4 g / L and adjust the pH value to 8.3 with dilute hydrochloric acid; disperse the hydroxylated composite thermal conductive filler obtained in step (1) in the Tris buffer solution, add dopamine hydrochloride and tannic acid, wherein the mass ratio of hydroxylated composite thermal conductive filler, dopamine hydrochloride and tannic acid is 7:3:1, stir the reaction at room temperature for 10 hours, after the reaction is completed, centrifuge, wash with deionized water and vacuum dry to obtain the surface functionalized modified composite thermal conductive filler.
[0075] The nitrogen-phosphorus synergistic halogen-free flame retardant is compounded from ammonium polyphosphate and melamine cyanurate in a weight ratio of 3.5:1.
[0076] The composite heat-resistant agent is composed of nano-cerium oxide, octavinyl POSS, and nano-boron carbide in a weight ratio of 0.5:0.5:1.
[0077] The preparation method of the above-mentioned single-layer silicone spiral heating wire includes the following steps:
[0078] (1) The heating alloy wire is wound in a spiral manner around the surface of the glass fiber skeleton pre-impregnated with a conductive polymer interface layer to obtain a core wire;
[0079] (2) The methyl vinyl silicone rubber raw rubber, the surface functionalized modified composite thermally conductive filler, the nitrogen-phosphorus synergistic halogen-free flame retardant, the composite heat resistant agent, the zinc borate and the vulcanizing agent are put into a kneader and mixed in the weight ratio described above. The mixing temperature is 115°C and the mixing time is 25 minutes to obtain silicone rubber compound.
[0080] (3) Pass the core wire obtained in step (1) through the center of the extruder head, and feed the silicone rubber compound obtained in step (2) into the extruder. The extruder head is set to the first temperature zone 52°C, the second temperature zone 68°C and the third temperature zone 82°C in sequence along the extrusion direction. The extruded core wire is coated on the surface and vulcanized with hot air at a temperature of 210°C for 6 minutes to obtain the single-layer silicone spiral heating wire.
[0081] Example 3
[0082] This embodiment provides a single-layer silicone spiral heating wire, including a core wire and a silicone rubber sheath covering the outer surface of the core wire.
[0083] The core wire comprises a glass fiber skeleton and a heating alloy wire spirally wound around the surface of the glass fiber skeleton. The glass fiber skeleton is E-glass fiber yarn with a diameter of 1.0 mm; the heating alloy wire is a nickel-chromium alloy wire with a diameter of 0.15 mm and a spiral winding pitch of 1.8 mm.
[0084] The surface of the glass fiber skeleton is pre-impregnated with a conductive polymer interface layer, and the method for preparing the conductive polymer interface layer is as follows:
[0085] (1) Add waterborne polyurethane emulsion with a solid content of 32wt% to deionized water to dilute to a working solution with a solid content of 11wt%. Add silane coupling agent KH550 and conductive carbon black under stirring, wherein silane coupling agent KH550 accounts for 1.8% of the total solid mass of the waterborne polyurethane emulsion and conductive carbon black accounts for 9wt% of the total solid mass of the waterborne polyurethane emulsion. Stir evenly to obtain impregnation solution.
[0086] (2) Immerse the glass fiber skeleton in the impregnation solution for 5 minutes, then remove it and dry it at 95°C for 35 minutes to form a film, that is, form the conductive polymer interface layer on the surface of the glass fiber skeleton.
[0087] The silicone rubber sheath is prepared from the following raw materials in parts by weight: 100 parts of methyl vinyl silicone rubber raw rubber; 35 parts of surface functionalized modified composite thermally conductive filler; 28 parts of nitrogen-phosphorus synergistic halogen-free flame retardant; 9 parts of composite heat resistant agent; 1.8 parts of vulcanizing agent 2,4-dichlorobenzoyl peroxide; and 5 parts of zinc borate.
[0088] The preparation method of the surface-functionalized modified composite thermally conductive filler is as follows:
[0089] (1) Carbon nanotubes and hexagonal boron nitride nanosheets were mixed at a weight ratio of 1:3.5 and added to a sodium hydroxide aqueous solution with a concentration of 11 g / L. The mixture was ultrasonically stirred at 62 °C for 1.8 hours, centrifuged, washed with deionized water until neutral, and vacuum dried to obtain hydroxylated composite thermally conductive filler.
[0090] (2) Prepare a Tris buffer solution with a concentration of 1.1 g / L and adjust the pH value to 8.4 with dilute hydrochloric acid; disperse the hydroxylated composite thermal conductive filler obtained in step (1) in the Tris buffer solution, add dopamine hydrochloride and tannic acid, wherein the mass ratio of hydroxylated composite thermal conductive filler, dopamine hydrochloride and tannic acid is 9:3.5:1, stir the reaction at room temperature for 7 hours, and after the reaction is completed, centrifuge, wash with deionized water and vacuum dry to obtain the surface functionalized modified composite thermal conductive filler.
[0091] The nitrogen-phosphorus synergistic halogen-free flame retardant is compounded from ammonium polyphosphate and melamine cyanurate in a weight ratio of 2.5:1.
[0092] The composite heat-resistant agent is composed of nano-cerium oxide, octavinyl POSS, and nano-boron carbide in a weight ratio of 0.35:0.7:1.
[0093] The preparation method of the above-mentioned single-layer silicone spiral heating wire includes the following steps:
[0094] (1) The heating alloy wire is wound in a spiral manner around the surface of the glass fiber skeleton pre-impregnated with a conductive polymer interface layer to obtain a core wire;
[0095] (2) The methyl vinyl silicone rubber raw rubber, the surface functionalized modified composite thermally conductive filler, the nitrogen-phosphorus synergistic halogen-free flame retardant, the composite heat resistant agent, zinc borate and vulcanizing agent are added into a kneader and mixed in the weight ratio described above. The mixing temperature is 125°C and the mixing time is 18 minutes to obtain silicone rubber compound.
[0096] (3) Pass the core wire obtained in step (1) through the center of the extruder head, and feed the silicone rubber compound obtained in step (2) into the extruder. The extruder head is set to the first temperature zone 58°C, the second temperature zone 72°C and the third temperature zone 78°C in sequence along the extrusion direction. The extruded core wire is coated on the surface of the core wire and vulcanized by hot air at a temperature of 240°C for 4 minutes to obtain the single-layer silicone spiral heating wire.
[0097] Comparative Example 1
[0098] The difference between this comparative example and Example 1 is that the surface-functionalized modified composite thermally conductive filler is replaced with an equal amount of unmodified alumina thermally conductive filler.
[0099] The dosage of other components, preparation methods and process parameters are the same as in Example 1.
[0100] Comparative Example 2
[0101] The difference between this comparative example and Example 1 is that the preparation method of the surface-functionalized modified composite thermally conductive filler is as follows:
[0102] (1) Carbon nanotubes and hexagonal boron nitride nanosheets were mixed at a weight ratio of 1:3 and added to a sodium hydroxide aqueous solution with a concentration of 10 g / L. The mixture was ultrasonically stirred at 60 °C for 2 hours, centrifuged, washed with deionized water until neutral, and vacuum dried to obtain hydroxylated composite thermal conductive filler.
[0103] (2) Disperse the hydroxylated composite thermally conductive filler obtained in step (1) in a mixed solvent of deionized water and ethanol (volume ratio 7:3), add 3wt% of silane coupling agent APTES, stir and react at 50°C for 30 minutes. After the reaction is completed, centrifuge, wash with deionized water and vacuum dry to obtain the silane coupling agent modified composite thermally conductive filler.
[0104] The dosage of other components, preparation methods and process parameters are the same as in Example 1.
[0105] Comparative Example 3
[0106] The difference between this comparative example and Example 1 is that the composite heat resistant agent is replaced by a ternary compound of nano-cerium oxide, octavinyl POSS, and nano-boron carbide with a binary compound of nano-cerium oxide and octavinyl POSS.
[0107] The total amount of the composite heat resistant agent is 8 parts by weight, wherein the weight ratio of nano-cerium oxide to octavinyl POSS is 0.4:0.6.
[0108] The dosage of other components, preparation methods and process parameters are the same as in Example 1.
[0109] Comparative Example 4
[0110] The difference between this comparative example and Example 1 is that the nano-boron carbide in the composite heat resistant agent is replaced with an equal amount of silica.
[0111] The dosage of other components, preparation methods and process parameters are the same as in Example 1.
[0112] Comparative Example 5
[0113] The difference between this comparative example and Example 1 is that the surface of the glass fiber skeleton was not impregnated with a conductive polymer interface layer, that is, the untreated glass fiber skeleton was used directly.
[0114] The dosage of other components, preparation methods and process parameters are the same as in Example 1.
[0115] Performance testing
[0116] The following performance tests were conducted on the single-layer silicone spiral heating wires prepared in Examples 1-3 and Comparative Examples 1-5. The first part was a performance test of the silicone rubber sheath material, with test samples taken from vulcanized test pieces made from the silicone rubber compounds prepared in each example and comparative example under the same vulcanization conditions (220℃ × 5 min). The second part was an overall performance test of the finished heating wire, with the test objects being the complete finished heating wires prepared in each example and comparative example.
[0117] Part 1: Properties of Silicone Rubber Sheath Material
[0118] (1) Tensile strength and elongation at break: The test was conducted in accordance with GB / T 528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber", using type 2 dumbbell-shaped specimens and a tensile speed of 500 mm / min.
[0119] (2) Thermal conductivity: The test was conducted according to ASTM D5470 (steady-state heat flow method), with a sample thickness of 2 mm, a hot electrode temperature of 80 °C, and a cold electrode temperature of 20 °C.
[0120] (3) Limiting oxygen index: The test shall be conducted in accordance with GB / T 10707-2008 "Determination of the flammability of rubber" - Method A (oxygen index method).
[0121] (4) Vertical burning rating: The test shall be conducted in accordance with GB / T 10707-2008 "Determination of the burning performance of rubber" - Method B (vertical burning method).
[0122] (5) Tensile strength retention rate after hot air aging: Refer to GB / T 3512-2014 "Accelerated aging and heat resistance test of vulcanized rubber or thermoplastic rubber in hot air", aging conditions 125℃×168h, after aging, the tensile strength is determined according to GB / T 528-2009, and the ratio of tensile strength before and after aging is calculated.
[0123] Part Two: Overall Performance of the Finished Heating Wire
[0124] (6) Electrical strength: The test shall be conducted in accordance with the provisions of 16.3 in GB 4706.8-2008. Take a heating wire sample with a length of 5m, immerse it in water containing about 1% sodium chloride at a water temperature of (20±5)℃, soak for 1h, then apply an AC current of 3000V and 50Hz between the conductor and the salt solution for 1min. It should not break down.
[0125] (7) Insulation resistance: The test shall be conducted in accordance with the provisions of 5.4.2 in QB / T 2163-2012. Take a heating wire sample with a length of 5m, apply a DC voltage of about 500V between the conductor and the salt solution, immerse it for 1 minute and then measure the insulation resistance.
[0126] (8) Bending life after heat aging: Take a heating wire sample with a length of 1m, first treat it with hot air aging at 125℃ for 168h (refer to GB / T 3512-2014), and after cooling to room temperature, conduct a bending test in accordance with the provisions of 21.111.1 in GB 4706.8-2008. Perform bending cycles at a frequency of 30 times per minute until the sample breaks or the electrical strength test breaks down. Record the number of bending cycles.
[0127] (0) Resistance change rate after energization cycle: Take a heating wire sample with a length of 5m and perform 500 energization-de-energization cycles at rated voltage (30 minutes of energization and 15 minutes of de-energization each time). After the cycle is completed, cool it to room temperature, measure the resistance value of the sample, compare it with the initial resistance value, and calculate the resistance change rate.
[0128] The test results are shown in Table 1.
[0129] Table 1 Performance Test Results
[0130]
[0131] As can be seen from the above performance test results, Examples 1-3 of the present invention exhibited excellent comprehensive performance in all tests. The silicone rubber sheath achieved high thermal conductivity while maintaining high elongation at break, and its tensile strength retention rate after aging in hot air at 125°C was extremely high. This proves that the synergistic effect of the biomimetic modified hybrid filler of polydopamine / tannic acid and the ternary composite heat-resistant agent successfully solved the core contradiction of traditional high-filler thermally conductive silicone: "high thermal conductivity inevitably sacrifices flexibility and aging resistance." At the finished product line level, all three examples passed rigorous electrical strength and insulation tests, and demonstrated excellent stability and extremely low resistance drift in simulated long-term use aging bending and energized cycle tests.
[0132] Comparative Example 1 replaced the hybrid filler of this invention with unmodified alumina thermally conductive filler. Due to the poor compatibility between alumina and the silicone rubber matrix and the high interfacial thermal resistance, the thermal conductivity and mechanical strength of the sheath dropped sharply. In the finished product test, the internal thermal stress accumulation caused by the poor thermal conductivity significantly deteriorated the bending life and energized cycle resistance stability after aging, demonstrating the importance of this invention in constructing an efficient thermally conductive network and maintaining flexibility through modification. Comparative Example 2 replaced the modification method with the conventional silane coupling agent APTES. Although the filler base was still carbon nanotubes and boron nitride, the coupling agent could not form a sufficiently dense interfacial buffer layer. The thermal conductivity and flexibility of the sheath were lower than those of the examples. This directly led to a decrease in the durability of the finished heating wire in the thermo-mechanical coupling aging test, verifying the advanced nature of the polydopamine / tannic acid co-deposition modification technology path of this invention. Comparative Example 3 reduced the ternary heat-resistant agent to a binary compound of nano-cerium oxide and POSS. The strength retention rate of the sheath after aging was significantly reduced. Due to the lack of rigid skeleton support from nano-boron carbide, the network structure of the silicone rubber was more prone to relaxation under long-term thermo-oxidative effects, reducing the physical and electrical stability of the finished heating wire under continuous heat load. Comparative Example 4 replaced nano-boron carbide with an equal amount of silica. The elongation at break of the sheath decreased significantly, indicating that the significant hardening effect of silica damaged the flexibility of the silicone. This brittle sheath was more prone to cracking during repeated bending aging and caused greater disturbance to the internal heating wire during energization cycles, highlighting the unique value of boron carbide in balancing heat resistance and flexibility. Comparative Example 5 removed the conductive polymer interface layer of the core wire, resulting in a precipitous drop in the bending life of the finished wire after aging and a sharp increase in the rate of change of resistance during energization cycles. This directly proves that the interface layer enhances the interlayer bonding force between glass fiber and silicone through chemical bonding and eliminates the interface of modulus abrupt change. At the same time, the conductive carbon black in the interface layer provides a weak conductive bypass when the heating wire breaks unexpectedly, so that the heating wire is free from premature mechanical breakage and fretting wear during the long-term use of the entire line. It is a key structure to ensure the long-term reliability of the heating wire.
[0133] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A single-layer silicone spiral heating wire, comprising a core wire and a silicone rubber sheath covering the outer surface of the core wire, wherein the core wire comprises a glass fiber skeleton and a heating alloy wire spirally wound around the surface of the glass fiber skeleton, characterized in that, The silicone rubber sheath is made from the following raw materials in parts by weight: 100 parts of raw methyl vinyl silicone rubber; 30-50 parts of surface-functionalized modified composite thermally conductive filler; 20-30 parts of nitrogen-phosphorus synergistic halogen-free flame retardant; 5-10 parts of composite heat resistant agent; 1.5 to 2.5 parts of vulcanizing agent; 3-5 parts zinc borate; The surface-functionalized composite thermally conductive filler is obtained by surface modification of a compound of carbon nanotubes and hexagonal boron nitride nanosheets with polydopamine and tannic acid. The composite heat-resistant agent is composed of nano-cerium oxide, octavinyl POSS, and nano-boron carbide.
2. The single-layer silicone spiral heating wire according to claim 1, characterized in that, The preparation method of the surface-functionalized modified composite thermally conductive filler includes the following steps: (1) Carbon nanotubes and hexagonal boron nitride nanosheets were mixed and added to an aqueous solution of sodium hydroxide. After ultrasonic stirring, centrifugation, washing with deionized water, and drying, hydroxylated composite thermally conductive filler was obtained. (2) Prepare a Tris buffer solution with a concentration of 1.0 to 1.5 g / L, and adjust the pH value to 8.0 to 8.5 with dilute hydrochloric acid; disperse the hydroxylated composite thermally conductive filler obtained in step (1) in the Tris buffer solution, add dopamine hydrochloride and tannic acid, stir and react for 6 to 12 hours. After the reaction is completed, centrifuge, wash with deionized water and dry to obtain the surface functionalized modified composite thermally conductive filler.
3. The single-layer silicone spiral heating wire according to claim 2, characterized in that, In step (1), the weight ratio of carbon nanotubes to hexagonal boron nitride nanosheets is 1:2 to 1:5; the concentration of sodium hydroxide aqueous solution is 8 to 12 g / L.
4. The single-layer silicone spiral heating wire according to claim 2, characterized in that, In step (2), the mass ratio of the hydroxylated composite thermally conductive filler, dopamine hydrochloride, and tannic acid is (6-10):(2-4):
1.
5. The single-layer silicone spiral heating wire according to claim 1, characterized in that, The nitrogen-phosphorus synergistic halogen-free flame retardant is composed of ammonium polyphosphate and melamine cyanurate in a weight ratio of (2-4):
1.
6. The single-layer silicone spiral heating wire according to claim 1, characterized in that, The mass ratio of nano-cerium oxide, octavinyl POSS, and nano-boron carbide is (0.3-0.6):(0.4-0.8):
1.
7. The single-layer silicone spiral heating wire according to claim 1, characterized in that, The surface of the glass fiber skeleton is pre-impregnated with a conductive polymer interface layer. The conductive polymer interface layer is prepared by mixing waterborne polyurethane emulsion, silane coupling agent KH550 and conductive carbon black, followed by dip coating and drying to form a film. The silane coupling agent KH550 accounts for 1.5% to 2.5% of the total solids of the waterborne polyurethane emulsion, and the conductive carbon black accounts for 5 to 10 wt% of the total solids of the waterborne polyurethane emulsion.
8. The single-layer silicone spiral heating element according to any one of claims 1-7 The method for preparing the wire is characterized in that, Includes the following steps: (1) The heating alloy wire is wound in a spiral manner on the surface of a glass fiber skeleton pre-impregnated with a conductive polymer interface layer to obtain the core wire; (2) Methyl vinyl silicone rubber raw rubber, surface functionalized modified composite thermally conductive filler, nitrogen-phosphorus synergistic halogen-free flame retardant, composite heat resistant agent, zinc borate and vulcanizing agent are added into a mixing mill according to the weight ratio described above and mixed to obtain silicone rubber compound. (3) Pass the core wire obtained in step (1) through the center of the extruder head, feed the silicone rubber compound obtained in step (2) into the extruder, extrude and coat the core wire surface, and obtain the single-layer silicone spiral heating wire after vulcanization.
9. The preparation method according to claim 8, characterized in that, In step (2), the mixing temperature is 110-130°C and the mixing time is 15-30 minutes.
10. The preparation method according to claim 8, characterized in that, In step (3), the extruder head temperature is 50-85℃, and the extrusion direction is set as the first temperature zone 50-60℃, the second temperature zone 60-75℃, and the third temperature zone 75-85℃; the vulcanization is carried out by hot air vulcanization, the vulcanization temperature is 180-250℃, and the vulcanization time is 3-8 minutes.
Citation Information
Patent Citations
A high thermal conductivity silicone rubber cable material, its preparation method and application
CN114213850B
High-temperature-aging-resistant flame-retardant silicone rubber and preparation method thereof
CN118562298A